2020
DOI: 10.1002/elan.201900612
|View full text |Cite
|
Sign up to set email alerts
|

1,4‐Benzoquinone Derivatives for Enhanced Bioelectrocatalysis by Fructose Dehydrogenase from Gluconobacter Japonicus: Towards Promising D‐Fructose Biosensor Development

Abstract: D‐fructose amount in food and beverages should be carefully controlled in order to avoid its overconsumption by human, which can lead to various metabolic diseases. Thus, the development of a low‐cost and portable (bio)sensors, which realize the on‐site monitoring of D‐fructose, is still highly required. In this work, we proposed several reagentless bioelectrochemical systems (BioESs) based on fructose dehydrogenase EC1.1.99.11 from Gluconobacter japonicus (FDH) and on 2‐arylamine‐1,4‐benzoquinone (ABQ) deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The elimination of compound 1 provided means of the correlating exponential functions with better statistic parameters. Our previous work [14] revealed that the BioAS with compound 1 exhibited extremely high reactivity in the case of oxidation of D‐fructose whilst in the case of D‐tagatose the same BioAS exhibited a moderate response. Such a difference shows that the compound 1 interacts with the active center of the enzyme and/or substrate intermolecularly in the way that high FDH reactivity in D‐tagatose oxidation is not achieved.…”
Section: Figurementioning
confidence: 96%
See 3 more Smart Citations
“…The elimination of compound 1 provided means of the correlating exponential functions with better statistic parameters. Our previous work [14] revealed that the BioAS with compound 1 exhibited extremely high reactivity in the case of oxidation of D‐fructose whilst in the case of D‐tagatose the same BioAS exhibited a moderate response. Such a difference shows that the compound 1 interacts with the active center of the enzyme and/or substrate intermolecularly in the way that high FDH reactivity in D‐tagatose oxidation is not achieved.…”
Section: Figurementioning
confidence: 96%
“…D‐Fructose is structurally similar to D‐tagatose, and both sugars differ only in the disposition of one hydroxyl group at the 4 th carbon atom [3a]. To check if FDH is able to catalyze the oxidation of D‐tagatose, we chose recently introduced by our research group reagentless bioamperometric systems (BioASs) with FDH [14].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Both organic and inorganic compounds can serve as mediators. Although redox mediation is well known, in recent years, several new types such mediators were designed and studied [ 62 , 63 ]. As stated above, mediators are also used in MSAs and MSSs [ 43 , 59 , 64 ].…”
Section: Principles Of Mss and Msamentioning
confidence: 99%